Análise da variação do clima organizacional em uma fábrica do Polo Industrial de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
This work aims to analyze the variation of the organizational climate in an industrial polo factory in Manaus, based on eight analysis of dimensions: communication, work environment, interpersonal relationship, management and leadership, work safety, benefits, motivation and organizational culture. It presents the concepts and definitions about the organization and the people, the organizational climate, the climate models and the factors that can influence the climate in the organization. The types of research classification are: applied, exploratory, quantitative, survey with data collection through questionnaire and longitudinal type. The measuring instrument was made available and applied in loco. The collection involved the socioeconomic data of the employees, as well as detailed information on the eight dimensions for analysis of the organizational climate. The data obtained were compared with the data from the climate research carried out in 2013. Descriptive statistics methods were used to calculate the mean percentages of the assertions with concordances and to calculate the reliability index, Cronbach's alpha, measurement. The conclusions reflect the state of the company in relation to the variation of the organizational climate occurred in the interval of October of 2013 to November of 2016. As results the interpersonal relationship dimension obtained the highest average of concordances with 86% and the dimensions with averages below 50% are the organizational culture with 39% and the benefits 45%. The overall average organizational climate was 66.38%. The reliability coefficient of Cronbach obtained was 0.892 classified as high. It is concluded that in general the organizational climate remains satisfactory, but that some measures can be implemented with the objective of improving the percentages of agreements, mainly in the dimensions organizational culture and benefits.
Keywords: Clima organizacional; Comportamento organizacional; Análise de clima; Pesquisa longitudinal; Empresa metalúrgica; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO